2022
DOI: 10.1097/mco.0000000000000849
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic scores and scales for appraising Nonalcoholic fatty liver disease and omics perspectives for precision medicine

Abstract: Purpose of reviewNonalcoholic fatty liver disease (NAFLD) is a rising epidemic burden affecting around 25% of the global population. Liver biopsy remains the reference for NAFLD. However, the application of several scales and clinical algorithms have been proposed to diagnose NAFLD using prediction questions and blood biomarkers. This review presents a summarized of the currently available and emerging diagnostic biomarkers and scores used to assess NAFLD.Recent findingsThe limitations of liver biopsy have fos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…In our study, we found that several noninvasive hepatic scores, which assessed different aspect and morbid features [ 26 ], appeared to be related to obesity in youngsters. Some indices have not been validated in children and might not be suitable for detecting and monitoring MASLD in children, but they may provide valuable information on different aspects of liver disease, such as composition, function, and lipid metabolism in clinical practice [ 57 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In our study, we found that several noninvasive hepatic scores, which assessed different aspect and morbid features [ 26 ], appeared to be related to obesity in youngsters. Some indices have not been validated in children and might not be suitable for detecting and monitoring MASLD in children, but they may provide valuable information on different aspects of liver disease, such as composition, function, and lipid metabolism in clinical practice [ 57 ].…”
Section: Discussionmentioning
confidence: 95%
“…Different indirect hepatic markers have been calculated, considering the necessary criteria and applying accepted formulas [ 26 ]. The equations are shown in Supplementary Table 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, biopsy or genetic studies are too risky, expensive, and complicated to be efficient in the risk factor scenario [ 44 ]. Thus, hepatic steatosis may be considered a surrogate metric for metabolic risk when evaluated through non-invasive techniques such as ultrasound, MRI, and transient elastography [ 45 , 46 ] and even validated serologic indices [ 47 ]. Several epidemiological studies have explored the association between non-invasively assessed SLD and metabolic and cardiovascular risk regarding quality of life [ 48 ], as well as the impact of lifestyle modification [ 49 ], incidence of T2DM [ 50 ], and incidence of cardiovascular events [ 51 ].…”
Section: Liver Steatotic Disease As a Potential Residual Cardiovascul...mentioning
confidence: 99%
“…Non-alcoholic fatty liver disease (NAFLD) is a prevalent liver condition characterized by the accumulation of excess fat in the liver, not caused by excessive alcohol consumption [1]. With its increasing prevalence globally, NAFLD has emerged as a significant public health concern [2]. Lifestyle factors play a crucial role in the development and progression of NAFLD, highlighting the importance of maintaining the high-quality lifestyle for both liver health and overall well-being [3].…”
Section: Introductionmentioning
confidence: 99%